1973
DOI: 10.1113/jphysiol.1973.sp010323
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the site of termination of static and dynamic fusimotor fibres within muscle spindles of the tenuissimus muscle of the cat

Abstract: 1. The site of termination of static and dynamic fusimotor fibres has been mapped by finding which intrafusal muscle fibres have been depleted of glycogen as a result of tetanic stimulation of single γ fibres. Long periods of stimulation coupled with occlusion of the blood supply were necessary to cause glycogen depletion. 2. In cat tenuissimus muscle, dynamic γ motor fibres always activated bag intrafusal muscle fibres, and occasionally chain fibres. Static γ fibres always activated chain fibres and frequentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
42
1

Year Published

1974
1974
1982
1982

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 24 publications
3
42
1
Order By: Relevance
“…From the observations of Boyd et al (1973) and from their own experiments Brown & Butler (1973) infer that 'the dynamic effects can occur with bag fibre contraction alone and static effects with chain fibre contraction alone, but not vice versa'. Such an assertion is correct concerning the dynamic effects since dynamic y axons innervating only chain fibres have never been found.…”
Section: Considerations Of the Functional Implications Of Fusimotor Amentioning
confidence: 98%
See 2 more Smart Citations
“…From the observations of Boyd et al (1973) and from their own experiments Brown & Butler (1973) infer that 'the dynamic effects can occur with bag fibre contraction alone and static effects with chain fibre contraction alone, but not vice versa'. Such an assertion is correct concerning the dynamic effects since dynamic y axons innervating only chain fibres have never been found.…”
Section: Considerations Of the Functional Implications Of Fusimotor Amentioning
confidence: 98%
“…Brown & Butler (1973) suggested that 'the inevitable unloading generated in the central portions of bag fibres by chain fibre activation is partly taken up by the simultaneous bag contractions. This may leave the spindle in a better state to respond quickly to a change from static to dynamic activation or may assist the dynamic y effects to come through when both sorts of y are activated simultaneously.'…”
Section: Considerations Of the Functional Implications Of Fusimotor Amentioning
confidence: 99%
See 1 more Smart Citation
“…Further, the motor control of spindles has been studied using the depletion of glycogen in particular intrafusal fibres following prolonged stimulation of their axons as the indicator (Brown & Butler, 1973, 1975 Barker, Emonet-D6nand, Harker, Jami & Laporte, 1975). These investigations are referred to in the Discussion.…”
mentioning
confidence: 99%
“…This is likely to be substantially longer for fibres activated by static axons (chains and bag 2; cf. Brown & Butler, 1973Bessou & Pages, 1975;Boyd, 1976a, b;Barker, Emonet-Denand, Harker, Jami & Laporte, 1976) than for dynamic activated fibres (bag 1), since statics but not dynamics tend to provoke propagated action potentials and occasionally even full-length activation of intrafusal fibres (Bessou fibres is smaller than the length of the bag 1 fibres (Barker, 1974;Barker et al 1976). Indeed, from the published data of Bessou & Pages (1975) it would appear that the speed of contraction induced by static fibres, measured by its time constant, exceeded dynamic action only by a factor of about 2.…”
Section: Speed Offusimotor Actionmentioning
confidence: 99%